Komunikasi Terapeutik Islami sebagai Strategi Penanggulangan Stunting pada Masyarakat Pesisir: Studi Kualitatif di Desa Rantau Panjang Kecamatan Pantai Labu - Mursyid, Abdillah; Zainun, Zainun; Syawaluddin, Syawaluddin (Lembaga Teewan Journal Solutions, 2026)
Stunting remains one of Indonesia's major public health challenges requiring multidimensional interventions beyond nutrition and medical services. This study aims to analyze the implementation of Islamic therapeutic communication in preventing stunting among coastal communities in Rantau Panjang Village, Pantai Labu District, Deli Serdang Regency, using a qualitative descriptive approach through in-depth interviews, observation, and documentation involving health workers, Posyandu volunteers, village officials, religious leaders, and community members. The findings reveal that Islamic therapeutic communication integrates interpersonal communication with Islamic values, including qaulan sadidan, qaulan layyinan, and qaulan ma'rufan, together with Qur'anic teachings and prophetic traditions, to strengthen public trust and the effectiveness of health promotion. Supporting factors include collaboration among village government, health workers, and religious leaders, while educational disparities, socioeconomic limitations, and cultural practices remain major obstacles. The study proposes an Islamic Therapeutic Communication Model integrating health communication, interpersonal communication, and religious values as a novel, community-based strategy for stunting prevention in religious societies.